Residents' view on resettlement issue of Vreoci: Sustainability or phrases - Petrić Jasna (Spatium, 2005)
Further expansion of Kolubara lignite basin indicates a necessity to limit future territorial encompass and spatial development of the present semi-urban settlement of Vreoci which is located some 50 km to the south from Belgrade. There is a part of Vreoci which has already been expropriated for the purposes of lignite exploitation, yet the possibility to resettle the town as a whole is still to be validated according to appropriate technical documentation and the feasibility study. Having that estimation of the total cost for such a venture so far showed to be unreliable, the Institute of Architecture and Urban & Spatial Planning professional team was engaged by the Electric Power of Serbia state company in order to prepare and conduct a questionnaire study on conditions for total resettlement of Vreoci. Before the actual fieldwork took place in June-July 2005, citizens of Vreoci were well informed on the questionnaire content and the interviewing period. The questionnaire was thus conducted through face-to-face interviews with one representative per household who could give all relevant information concerning this study. Though the questionnaire covered information on households as well as on their premises (general facts about constructions built on the household lots), this paper is focused on the first type of information and makes an emphasis on residents' opinion regarding viable/ sustainable options for their resettlement.